Ideology without Emblems: The Quiet Metamorphosis of Hizbut Tahrir Indonesia through Grassroots Da‘wah - Mulyadi, Muhammad Mus; Azka, Ibnu; Tsauro, Muhammad Ahalla (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2025)
Although Hizbut Tahrir Indonesia (HTI) was officially banned by the Indonesian government in 2017, its movement and ideological influence continue at the grassroots level in a more adaptive form. This phenomenon is clearly visible in various activities among urban youth communities in Makassar. Therefore, this article aims to explore the movement to spread and strengthen the ideological basis of Hizbut Tahrir Indonesia after it was banned, through grassroots da’wah among youth communities in Makassar. This study employs a qualitative method with an ethnographic approach. The study focuses on the Genk Pemuda Surga (GPS) and Makassar Bina Taqwa (MBT) communities. Data collection was conducted through participant observation, in-depth interviews, document analysis, and observation of digital activities. Data collection was carried out from January to June 2025. The data were analyzed thematically through transcription, coding, and pattern identification to reveal the processes of ideology internalization and the da’wah strategies used by the two communities. This study found that even though Hizbut Tahrir Indonesia no longer maintains a formal or symbolic presence as an organization, the dissemination of its ideology has metamorphosed and continues to operate through non-formal but structured forms of da’wah. In this context, the Genk Pemuda Surga (GPS) and Makassar Bina Taqwa (MBT) communities use informal religious spaces, such as youth study circles, weekly gatherings, community-based activities, and digital platforms, to spread an exclusive Islamic narrative that often rejects Indonesia’s democratic political system. These findings indicate that banning organizations does not necessarily eliminate ideologies, but instead encourages the transformation of da’wah into a more fluid, relational, and cultural form.